2020
DOI: 10.1002/brb3.1731
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the recovery outcome of poststroke cognitive impairment after cluster needling of scalp acupuncture therapy based on functional near‐infrared spectroscopy

Abstract: Background Cognitive impairment often arises in patients suffered from stroke. Acupuncture is a recommended treatment option for stroke by the World Health Organization (WHO) and has been shown to improve the cognitive function of patients with poststroke cognitive impairment (PSCI). Methods In the present study, we assessed the efficacy of scalp acupuncture with cluster needling on PSCI patients. Fifty six PSCI patients were randomly separated into the reference group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…One trial (Li and Jiao, 2014) might be the likely source of heterogeneity, which did not change the sensitivity analysis result when it was excluded from the pooled process (see Supplementary Table 4). When comparing acupuncture plus WM with WM alone, a statistically significant difference was also revealed without an apparent degree of heterogeneity (SMD −0.34, 95% CI −0.52 to −0.16, I 2 = 0%, p = 0.0003, five studies, see Figure 6B) (Chu et al, 2008;Zhang et al, 2008;Shi et al, 2009;Yang et al, 2016;Chen et al, 2020). One study (Xiong et al, 2020) showed that acupuncture plus UC got a better ADL Scale score than the UC alone group (MD −5.43, 95% CI −7.27 to −3.59, p < 0.0001, see Figure 6C).…”
Section: Activities Of Daily Living Scalementioning
confidence: 96%
See 4 more Smart Citations
“…One trial (Li and Jiao, 2014) might be the likely source of heterogeneity, which did not change the sensitivity analysis result when it was excluded from the pooled process (see Supplementary Table 4). When comparing acupuncture plus WM with WM alone, a statistically significant difference was also revealed without an apparent degree of heterogeneity (SMD −0.34, 95% CI −0.52 to −0.16, I 2 = 0%, p = 0.0003, five studies, see Figure 6B) (Chu et al, 2008;Zhang et al, 2008;Shi et al, 2009;Yang et al, 2016;Chen et al, 2020). One study (Xiong et al, 2020) showed that acupuncture plus UC got a better ADL Scale score than the UC alone group (MD −5.43, 95% CI −7.27 to −3.59, p < 0.0001, see Figure 6C).…”
Section: Activities Of Daily Living Scalementioning
confidence: 96%
“…As a result, 48 RCTs, published from 1992 to 2020, involving 3,778 patients with VCI met the eligible criteria and were synthesized in the final quantitative meta-analysis (Huang et al, 1992;Mo et al, 2000a,b;Zhao et al, 2000Zhao et al, , 2009Jiang et al, 2003Jiang et al, , 2019Liu et al, 2006;Niu and Liu, 2007;Chu et al, 2008;Liu Y. et al, 2008;Liu Z. B. et al, 2008;Zhang et al, 2008Zhang et al, , 2015Zhang et al, , 2019Chen et al, 2009Chen et al, , 2015Chen et al, , 2020Li et al, 2009Li et al, , 2019Meng et al, 2009Meng et al, , 2020Shi et al, 2009;Yin et al, 2011;Lin et al, 2012;Li P. et al, 2012;Li S. et al, 2012;Li W. et al, 2012;Teng and Lai, 2012;Pan and Ai, 2013;Zhao and Xu, 2013;Cao et al, 2014;Li and Jiao, 2014;Cui et al, 2015;Luo et al, 2015;Yang et al, 2016Yang et al, , 2019Tan et al, 2017;Wang and Wang, 2017a,b,c;Cheng et al, 2018;Feng et al, 2019;Hu et al, 2019;Qu et al, 2020;…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations